Differential responses to European policies: A comparison - Adrienne Héritier; Christoph Knill (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2000)
Community legislation is unquestionably a factor to be reckoned with in member-state policy making. But the extent and mode of its impact on domestic policies and administrative structures will depend on the existing policy practices and the political and institutional structures of the country in question. In cases where there is a mismatch between an established policy of a member state and a clearly specified European policy mandate, there will be an expectation to adjust, which in turn constitutes a precondition for change. Assuming the existence of a need for change, the ability to adapt will depend on the policy preferences of key actors, and the capacity of institutions to implement reform, realize policy change, and administratively adjust to European requirements. The policy preferences of key actors are influenced by the distributional consequences of the policies to be adopted (Milner 1996); the capacity to change depends on the degree of integrated political leadership, caused by a lack of formal veto points (Tsebelis 1995), or a decisional tradition capable of surmounting formal and factual veto points by way of consensual tripartite decision making. Where there is a divergence of mismatch between European and national policies, and the policy preferences of political leaders are defined by a willingness to adapt, the absence of formal veto points and a cooperative decisional tradition will enhance the capacity to change and to adjust administrative structures in compliance with European policy mandates...
Keywords: 330; EU-Politik; Deregulierung; Verkehrsgewerbe; Vergleich; Deutschland; Italien; Großbritannien; Niederlande; Frankreich